Des plantes qui prêchent. Représentations des végétaux dans des textes exemplaires médiévaux : approche éco-critique - Viviane Genest (Studia Romanica Posnaniensia, 2025)
Living world and nature has been perceived through the book metaphor revealing God presence in his creation. Thus, early medieval scientific texts has been composed in order to be used in preaching and spiritual context, to illustrate faith discourses. But despite of these orientations, one could read in texts a different perception of living world, especially plants beings. Then, without neglecting the deep allegorical dimension of these discourses, one can imagine ecocritical readings that pay close attention to the relationships human and plants could elaborate in medieval ecosystems, at least, literary one.